Immersive and Counter-Immersive Styles of Writing AIDS in Sindiwe Magona’s Beauty’s Gift and Kgebetli Moele’s The Book of the Dead: A Didactic Approach to Writing AIDS - Soldati-Kahimbaara, Kulukazi (Archīum Ateneo, 2024)
Two distinct responses to the growing body of literature on AIDS, according to Joseph Cady, are immersive and counter-immersive AIDS writing. The former addresses itself to the denial which has dominated worldwide reaction to AIDS, and confronts this denial squarely in an effort to undo it. Central to immersive writing is an attempt to thrust the reader into a direct imaginative confrontation with the special horrors of AIDS, and thus forcing him/her to deal with these horrors with no relief or buffer provided by the writer. In Magona’s Beauty’s Gift, this is evident when Beauty wastes away suddenly, but denies that something is seriously wrong and in fact colludes with her husband (the alleged culprit who infects Beauty with HIV) in an effort to avoid the stigma and shame associated with admitting she is infected with HIV and AIDS by maintaining the denial and silence surrounding the disease. The latter also recognizes the dreadfulness of the disease and indicates the problem of denial in the larger society, but its stance towards the denial seems to be deferential. As is the case with counter-immersive writing, Moele’s novel, The Book of the Dead, focuses on characters who are themselves in various degrees of denial about AIDS, and it treats its readers the way the characters handle their disturbing contact with AIDS, protecting them from a jarring confrontation with the subject by using a variety of distancing devices. What the two novels succeed in revealing is that free availability of knowledge about how people get infected with HIV, how HIV spreads, and how individuals can protect themselves against infection by either condomizing, abstinence, etc., does not always translate into changing sexual behavior, and this applies to people of all races, the rich and the poor, the educated and uneducated, and the young and the old alike.